'Day beautiful: The re-presentation and transformation of the bakla in the selected films of Jun Lana - Roquero, Jenno (Animo Repository, 2024)
The bakla are staple and thriving characters in Philippine cinema. However, the question of what the bakla or who the bakla are remains a significant concern since they are still objects and subjects of condemnation and discrimination no matter how (in)visible they are in the country and Philippine cinema. This study focuses on two aspects of the cinematic portrayal of the bakla: their “re-presentation” and their “transformation” using the eight (8) bakla-themed films written and directed by Jun Lana: Roxxxanne (2007), Bwakaw (2012), Bakit Lahat Ng Gwapo May Boyfriend? (2016), Die Beautiful (2016), Ang Dalawang Mrs. Reyes (2018), Kalel,15 (2019), Big Night! (2021), and About Us but not About Us (2023). Through close reading, informed by various Philippine gay theories, theories of kabaklaan, and New Queer Cinema, this study reveals the following about the bakla and kabaklaan in films: (1) the effeminate bakla still thrives in Philippine cinema – but with a difference; (2) the masculine bakla is the new macho gay/machine; (3) the bakla are not asexuals; (4) the bakla are out and proud; (5) the bakla achieve the happy ending they deserve; (6) the bakla reimagine multiple queer futures. Through the films of Jun Lana, the bakla transform this derogatory term into a spectacle – a celebration of their multiplicity and plurality. The bakla become a polymorphous signifier for evolving identities that resist the fixed identity imposed by the heteropatriarchal ideologies. This study highlights the fluid re-presentation of the bakla as an all-encompassing term that refers to the various forms and performativity of kabaklaan, male homosexuality, and queerness. Like the queer, which has become an umbrella term for all nonnormative gender identities and sexualities, the bakla denote alternative forms of queerness – not as a fixed cultural and gender identity/category but as a continuous exploration of Filipino identity, sexuality, and gender performativity. This study underscores the place of Jun Lana as a gay director and the significance of his queer films that embody the discursive and transformative power of the bakla in Philippine cinema – a new filmic imagination, a new image of the nation – hence, the bakla continuously envision the ‘day beautiful. Keywords: Bakla, Jun Lana, Philippine Queer Cinema, Re-presentation, Transformation